Improving soil and water management for agriculture: insights and innovation from Malta - Hallett, Stephen; Sakrabani, Ruben; Thompson, Andrew J.; Deeks, Lynda K.; Knox, Jerry W. (Malta College of Arts, Science & Technology, 2017)
Maltese soil resources are a precious and finite natural resource of great agricultural, environmental, and cultural value. They have been subject to human influence over a considerable time and, owing to prolonged intensive land use, have suffered from degradation by erosion, loss of organic matter, structural deterioration, and contamination from excess nitrates, agrochemicals, and salinity. Similarly, water resources (both quantity and quality) in Malta are also under severe stress owing to socio-economic development, over-abstraction for agricultural irrigation and from diffuse pollution. This paper briefly explores the key soil and water challenges facing farmers and the agricultural sector in Malta. Selected technology based and management innovations to improve resource use efficiency, sustain productivity, and support the agricultural sector are identified and discussed. The evidence forms part of FOWARIM ‘Fostering water-agriculture research and innovation in Malta’, an EC H2020-funded twinning project that is building research capacity, supporting knowledge exchange to practitioners, and providing evidence to inform policies for government and the agricultural sector in Malta.
Keywords: agriculture; soil; nutrient; irrigation; management; maps; water resources